STRATEGI KOMUNIKASI PEMASARAN BISNIS TIKET ONLINE - Agung Slamet Prasetyo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
Study was conducted to determine the marketing communications strategy used an online business. With the case of the online ticket business Tiket2.com. The purpose of this study was to determine the marketing communications strategies used Tiket2.com in his business, and the reasons for those strategies. In this online ticket business, before knowing what strategy to use, should be set in advance the objectives to be achieved in implementing this strategy. And objectives are set forth in segmenting, targeting and positioning. Then to achieve these objectives the strategy drafted in the Product, Place, Price and Promotion, known as the Marketing Mix. Marketing Communication Mix consists of a specific mix of advertising, public relations, personal selling, sales promotion and direct marketing tools that companies use to communicate in a persuasive customer value and build relationships with customers. The study was conducted with qualitative methods. Research shows that advertising on google.com is a means of effective marketing communication. Public Relations by means of online using a blog is the primary support in advertising on google.com.